(3GdSaQ GdeSJhaj aj TQM aQGFV GdMhais - (3eMeO Hf jhSa GdJfhSis; (3GdMhaj , Ydj Hf EHQGgje Hf SYjO, CHh GdMSf,J (B430 (3g` s
(3ChdgG (B:s
(3hHYOg cJGH GdTjN GdEeGe GdYdGeI CHj GdbGSe GdMhai ef MSGH eSGFd GdaQGjV s
(3BNQgG (B:s
(3jJbSe YdjgeG LRA HYO LRA KdGKG eKdkG ddBNQ s
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B250 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B5s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1246s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Yde GdaQGFVs